A Political, Economic, Social, Technology, Legal and Environmental (PESTLE) Approach for Risk Identification of the Tidal Industry in the United Kingdom - Kolios, Athanasios J.; Read, G. (MDPI, 2013)
This paper presents a comprehensive analysis of renewable and especially tidal energy through a political, economic, social, technology, legal and environmental (PESTLE) analysis approach and by reviewing the most up to date relevant literature. The study focuses on the United Kingdom given the favourable environmental resources for such technologies; the number of different design concepts that are currently under development as well as the research funding that has been invested over the last few years. Findings of the analysis identify the risks and multiple stakeholders involved at all stages of the tidal energy projects development from the conceptualization of the design, right through to decommissioning. Many of the stakeholders present benefits to the tidal developers through funding, incentives and knowledge sharing, but at the same time they also present potential risks to the future of projects. This is mostly down to different approaches of the most important aspect of tidal energy that needs to be considered, making it hard for technologists and developers to equally address all requirements. From this research it can be concluded that several of these risks can be mitigated early on providing that particular stakeholders are involved at the correct stage of a project.